Phytomedicine and the COVID-19 pandemic - Sohail, Muhammad Irfan (Phytomedicine, 2021)
Coronavirus disease broke out as unexplained pneumonia in Wuhan, China. The disease soon became a pandemic and was formally named as coronavirus disease or COVID-19. The causative virus has been named as SARS-CoV-2 by the International Committee on Taxonomy of Viruses. The most common complication in COVID-19-affected patients appears to be acute respiratory distress syndrome. At present, mainly symptomatic treatments are being given to COVID-19 patients, and no drug has been proved to cure the disease. There has been vying among pharmaceutical and researcher to devise a cure. The phytotherapy or the phytomedicines have been acknowledged as effective immunity booster and potential to eliminate the viral infection. The Chinese approach toward traditional herbal medicines has already being acknowledged as antiviral and RNA synthesis inhibitors globally. The secondary metabolites of plants such as alkaloids, flavonoids, phenolic acids, and terpenoids have been the source of countless medicinal compounds. For example, well-known antimalarial chloroquine phosphate (analogue of quinine, originally extracted from the bark of cinchona tree) has broad-spectrum antiviral activities. Antiviral phytomedicines have already been used in past two coronavirus outbreaks, that is, SARS-CoV and MERS-CoV. Ethnobotany or the folklore knowledge of medicinal plants, for instance, has also played a major role in the development of new drugs for centuries. Some species such as Lycoris radiata, Artemisia annua, Lindera aggregata, Isatis indigotica, Torreya nucifera, and Houttuynia cordata have already have proven their efficacies against certain ailments. Different plant parts can be consumed as raw or be modified into decoctions and tea for maximizing their effectivity. Moreover, phytochemicals can be regarded as best source of alternative and cheaper counterparts to synthetic medicines. Specifically, plants possessing antiinfluenza and antimalarial activities are potential candidates. Therefore this chapter will elucidate the phytoactive compounds and their sources and efficiencies in mitigating the COVID-19. This chapter will also serve a guideline to phytotherapy-based industries and public health.